Michigan Plecoptera (Stoneflies): distribution patterns and an updated species list - Grubbs, Scott A. (Illiesia, 2012)
The stonefly fauna of Michigan is updated, increasing the number of species verified from the state to 68. Twelve species are reported for the first time while two species of Isogenoides and Taeniopteryx maura (Pictet) are removed. Eight of the nine Nearctic families are represented. Peltoperlidae is the solefamily not present in Michigan. Perlodidae (18 species) and Perlidae (17 species) were the most speciose families in the state, and Isoperla (Perlodidae) was easily the most species-rich genus (11). Within the Michigan portion of the four Great Lakes bordering the state, eight species have been obtained from Lake Superior compared to none from Lake Erie and two species total collected from Lake Huron and Lake Michigan. Half (34 species) of the state fauna appears to be distributed only in the northern Lower Peninsula and Upper Peninsula, while 27 species are broadly distributed throughout the state. We discuss, in detail, 25 species that appear to be rare or uncommon and sparsely-distributed. This group includes four species known only from historical records (prior to 1950) and two that are presumably extirpated from the state (Helopicus nalatus (Frison) and Attaneuria ruralis (Hagen)).
Keywords: entomology; Michigan; Plecoptera; Nearctic; extirpation